2019
DOI: 10.1155/2019/1719829
|View full text |Cite
|
Sign up to set email alerts
|

A Subtle Network Mediating Axon Guidance: Intrinsic Dynamic Structure of Growth Cone, Attractive and Repulsive Molecular Cues, and the Intermediate Role of Signaling Pathways

Abstract: A fundamental feature of both early nervous system development and axon regeneration is the guidance of axonal projections to their targets in order to assemble neural circuits that control behavior. In the navigation process where the nerves grow toward their targets, the growth cones, which locate at the tips of axons, sense the environment surrounding them, including varies of attractive or repulsive molecular cues, then make directional decisions to adjust their navigation journey. The turning ability of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
102
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(102 citation statements)
references
References 281 publications
0
102
0
Order By: Relevance
“…It may inhibit the axon growth by stimulating neurons to induce RhoA and ROCK (Rho-associated coiled-coil protein kinase) expression [ 5 ]. It has been confirmed that RGMa may cause cone collapse by activating downstream Rho-GTPase activity [ 26 ]. In addition, RGMa can regulate the phosphorylation of collapse response mediator protein-2 (CRMP-2) by activating Rho-kinase and glycogen synthase kinase 3 β (GSK-3 β ) signaling pathways, thus regulating the axonal shortening [ 26 ].…”
Section: Role Of Rgma In Cns Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…It may inhibit the axon growth by stimulating neurons to induce RhoA and ROCK (Rho-associated coiled-coil protein kinase) expression [ 5 ]. It has been confirmed that RGMa may cause cone collapse by activating downstream Rho-GTPase activity [ 26 ]. In addition, RGMa can regulate the phosphorylation of collapse response mediator protein-2 (CRMP-2) by activating Rho-kinase and glycogen synthase kinase 3 β (GSK-3 β ) signaling pathways, thus regulating the axonal shortening [ 26 ].…”
Section: Role Of Rgma In Cns Pathologymentioning
confidence: 99%
“…It has been confirmed that RGMa may cause cone collapse by activating downstream Rho-GTPase activity [ 26 ]. In addition, RGMa can regulate the phosphorylation of collapse response mediator protein-2 (CRMP-2) by activating Rho-kinase and glycogen synthase kinase 3 β (GSK-3 β ) signaling pathways, thus regulating the axonal shortening [ 26 ]. Two independent c-RGMa and n-RGMa can activate different intracellular pathways to regulate neuronal survival: (1) in general, c-RGMa combines with Neogenin to activate RhoA through Unc5 and LARG ( Figure 1(b) ) [ 27 29 ].…”
Section: Role Of Rgma In Cns Pathologymentioning
confidence: 99%
“…Despite the identification of novel guidance cues and mechanisms, how a limited number of cues generate the complex diversity of axonal trajectories remains a fascinating puzzle. The current understanding of the cellular and developmental regulation of axonal guidance pathways has been discussed extensively in recent reviews [ 4 , 7 , 13 , 14 , 15 ]. Beyond these mechanisms, posttranslational modifications contribute significantly to regulating axon guidance pathways [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we focus on guidance cue/ receptor families that are critical to form major tracts in the cerebral cortex, cerebellum, and hippocampus: Semaphorin/Neuropilin, Netrin/DCC, and Slit/Robo. 3 We highlight tracts in each region-the CC in the cerebral cortex, climbing and mossy fibers in the cerebellum, and mossy fibers in the hippocampus. We aim to explore FASD pathology potentially associated with axon guidance in these regions.…”
Section: Introductionmentioning
confidence: 99%